Mucosal Vaccines against Bacterial and Viral Pathogens - A. N. Suvorov; Т. A. Kramskaya; T. V. Gupalova; Yu. A. Desheva; G. F. Leontieva (Эпидемиология и вакцинопрофилактика, 2023)
The mucosal membranes of the human body play a crucial role in the development, maintenance, and regulation of barrier functions and immune homeostasis, representing an integral component of the overall immune system. Mucosal vaccines elicit immune processes in the lymphoid tissue associated with the mucosal membranes. A critical objective of mucosal immunization is the identification of an antigen delivery vector capable of ensuring optimal vaccine efficacy. The authors of this article have conducted extensive research on the probiotic properties of enterococci over an extended period. They employ a safe and beneficial probiotic strain, Enterococcus faecium L3, as a delivery vector for vaccine antigens. Initially, the gene encoding the pathogenicity factor Bac, derived from group B streptococci (Streptococcus agalactiae), was successfully integrated into the genome of the probiotic strain E. faecium L3. Intravaginal, oral, and intranasal mucosal immunization methods utilizing the L3-Bac+ probiotic, which expresses antigenic determinants of pathogenic streptococci, were found to confer protection against bacterial infection in laboratory animals. Subsequently, recombinant technologies were refined, leading to the development of a universal method for incorporating a region of interest from the gene into the structure of the major pili protein gene of E. faecium L3. Using this technology, candidate vaccines against various infections, including Streptococcus pneumoniae, influenza A virus, and SARS-CoV-2 following the onset of the Covid-19 pandemic, have been obtained and tested. In this study, alongside the presentation of our own data, the challenges associated with utilizing recombinant probiotic bacteria as vectors for vaccine antigen delivery are discussed.